1997
DOI: 10.1111/j.1746-1561.1997.tb03443.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐Disciplinary Curriculum for 11‐ to 13‐Year‐Olds: Immunization, Plus!

Abstract: A sixth grade curriculum entitled "Immunization, Plus!" Was developed to promote adolescent immunization. This targeted immunization curriculum utilized contemporary learning theory and innovative teaching approaches and styles to maximize acceptability among educators. Because instructional time in school was limited, a thematic curriculum was created to embed immunization and communicable disease content within mathematics, science/health, and language arts units. The curriculum, which reflected the theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Innovative multidisciplinary curricula have been developed to promote vaccine education in schools 35,36 ; these curricula can be used to meet existing educational goals in several topic areas, thereby reducing competition between health education and other academic priorities. 36 Vaccine manufacturers have supplied temporary grants to develop vaccine education for students and staff; good examples include the "Roll up Both Sleeves!" curriculum and the "Give It a Shot" toolkit, both from the American School Health Association (Fig 3).…”
Section: Educating Students Teachers and Staffmentioning
confidence: 99%
“…Innovative multidisciplinary curricula have been developed to promote vaccine education in schools 35,36 ; these curricula can be used to meet existing educational goals in several topic areas, thereby reducing competition between health education and other academic priorities. 36 Vaccine manufacturers have supplied temporary grants to develop vaccine education for students and staff; good examples include the "Roll up Both Sleeves!" curriculum and the "Give It a Shot" toolkit, both from the American School Health Association (Fig 3).…”
Section: Educating Students Teachers and Staffmentioning
confidence: 99%
“…20 In keeping with other current health education programs, the project offered teacher training and support to facilitate implementation of the curriculum and gave teachers the choice of teaching just key lessons or of integrating materials into their own lesson plans. 21 As a corollary to education efforts, the project sought to reach parents, who serve as both protectors of their children's skin and important role models. This report describes the school and child care aspects of the intervention as well as the evaluation of the impact on classroom teaching, school policy, and children's knowledge and attitudes.…”
mentioning
confidence: 99%
“…The same program found that sending students home with printed information was sufficient for most parents to give informed consent, though incentives were influential in getting the consents returned ( Woodruff, Unti, Coyle, & Boyer‐Chuanroong, 1996). Adolescents, parents, and school personnel were more likely to seek vaccinations and participate in vaccination programs when they received information about: (a) communicable diseases, (b) the role of immunizations in preventing diseases, and (c) the importance of a communitywide response to health threats ( Glik et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three major challenges to the success of school‐based immunization programs are identified in the literature. First, Glik et al (1997) noted that trying to add more health education to an already full school curriculum is problematic. Second, Cassidy et al (1997) noted that vaccine procurement presents a challenge when restrictions tied to vaccine funding sources lead to complex screening of students at the vaccination site.…”
Section: Literature Reviewmentioning
confidence: 99%